2015
DOI: 10.1002/jmri.25011
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient (ADC) measurement in ovarian tumor: Effect of region‐of‐interest methods on ADC values and diagnostic ability

Abstract: The ROI shape influences ADC values and the optimal cutoff ADC values for differentiating benign from malignant ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 15 publications
4
35
0
1
Order By: Relevance
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
“…Prior studies assessed the interobserver agreement of ADC quantification by using different methods in various tumors . However, none of the studies on DW‐MRI of pleural disease evaluated the measurement variability of the ADC between different readings or readers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-tumor ROI can overcome this problem, however, it is a time consuming process, which limits its clinical application (12). The influence of ROI selection methods on the ADC measurements has been evaluated in the liver (13), ovaries (14), pancreas (1115), and breast (16). However, to our knowledge, no previous study has addressed the influence of the three different ROI selection methods on the ADC measurements, and their diagnostic abilities for differentiating benign from malignant orbital tumors.…”
Section: Introductionmentioning
confidence: 99%